2002
DOI: 10.1038/oby.2002.100
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Environmental Influences on Body‐Fat Measures among African‐American Twins

Abstract: Results: In men, additive genetic effects accounted for 77% of the variance in WC, 59% in WHR, and 89% in BMI. In women, additive genetic effects accounted for 76% of the variance in WC, 56% in WHR, and 73% in BMI. The remaining variance in both men and women was attributed to unique environmental effects (WC, 21%; WHR, 36%; BMI, 11% in men and WC, 22%; WHR, 38%; BMI, 27% in women) and age (WC, 2%; WHR, 5% in men and WC, 2%; WHR, 6% in women). When BMI was controlled in the analysis of WC and WHR, it accounted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…The WHR has been determined by both environmental factors, such as physical activities, cigarette smoking and alcohol consumption, and genetic factors in different degrees among ethnic populations [8,9]. In African-Americans, 59% of the variance of the WHR in men and 56% of the variance of the WHR in women were attributed to genetic factors [10].…”
Section: Discussionmentioning
confidence: 99%
“…The WHR has been determined by both environmental factors, such as physical activities, cigarette smoking and alcohol consumption, and genetic factors in different degrees among ethnic populations [8,9]. In African-Americans, 59% of the variance of the WHR in men and 56% of the variance of the WHR in women were attributed to genetic factors [10].…”
Section: Discussionmentioning
confidence: 99%
“…The heritability of BMI ranged from 45 to 85% in a comparative study of twin cohorts in eight countries, 11 and heritability estimates for WC have varied between 45 and 77% in previous twin studies. [12][13][14][15] Genetic effects have also been demonstrated for weight gain. 16,17 The heritability of exercise participation ranged from 27 to 70% in a large pooled twin sample from seven countries.…”
Section: Introductionmentioning
confidence: 99%
“…Heritability estimates for both systolic blood pressure (SBP) and diastolic blood pressure (DBP) are between 40 and 60%, 5 and the heritability for body mass index (BMI) is also substantial. [6][7][8] These estimates raise the possibility that common genetic susceptibility may account for the association. Several previous twin and family studies have shown that the association between blood pressure (BP) and BMI is partly attributed to a common set of genetic factors, 5,9-11 although another study investigating the differences in monozygotic (MZ) twins showed that even in the absence of genetic influences, obesity may still be significantly associated with BP.…”
Section: Introductionmentioning
confidence: 99%